Cities and the lives of university academics. (August 2014) - Yonezawa, Akiyoshi; Sato, Kaoru; Kawano, Ginko
Abstract Although the relationship between cities and universities is a commonly discussed topic, the so‐called 'world class universities' and 'global cities' in East Asia do not always fit into one single cosmopolitan model. Focusing on the case of Tokyo and Japan, the authors of this paper examine the mobility patterns, academic and social lives, and gender differences of university academics as representative knowledge workers. Using original survey results, the authors first create a hierarchical structure of academic mobility patterns in Japan, and then argue that Tokyo, as the capital of Japan, is a centre of the intellectual network through its education and training function.